Penguatan Kelas Ibu pasca salin dan Menyusui sebagai upaya Pemenuhan Nutrisi - Rizki Amalia; Achmad Syafiuddin; Fauziyatun Nisa’; Yunik Windarti; Ulliyatul Laili; Winawati Eka Putri (Universitas Majalengka, 2024)
Postpartum mothers really need nutrition because nutrition can affect breast milk production, postpartum recovery, and other influences on the postpartum mother's survival. If a postpartum mother experiences malnutrition, the postpartum mother can suffer from diseases such as anemia. This incident has an impact on the baby, namely that it can experience growth and development problems, young babies get sick and get infections. Recovery during the postpartum period can be accelerated by fulfilling nutrition for postpartum mothers which includes good nutrition, balanced nutrition, and increasing breast milk production. If nutritional disorders such as malnutrition, iron deficiency and anemia can inhibit wound healing. Community service activities were carried out for 1 month with 28 postpartum mothers participating in the Wonokromo subdistrict RW hall. This activity involves providing health education using power point media, LCD and leaflets about fulfilling nutrition during postpartum using the lecture and question and answer method. Measuring the level of knowledge by conducting a pre-test before providing education, followed by a post-test after providing education. The results of this community service activity showed that the level of knowledge during the pre-test was obtained with a score of 32.1%, while during the post-test the level of knowledge increased to 89.3%. The conclusion of this community service activity is that there is an increase in the knowledge of postpartum mothers in fulfilling nutrition.